The Impact of Artificial Intelligence Adoption on Human Resource Management Practices Today - Fitra Mulya; Raden Roro Lia Chairina; Sulistiyanto Sulistiyanto (Mandalika Journal of Business and Management Studies, 2026)
Artificial Intelligence (AI) has emerged as a transformative technology that significantly influences contemporary Human Resource Management (HRM) practices. This study examines the impact of AI adoption on HRM functions, focusing on its opportunities, challenges, ethical implications, and strategic contributions to organizational performance. The research employed a qualitative approach using library research and a narrative literature review. Twenty peer-reviewed publications published between 2021 and 2026 were systematically selected based on predefined inclusion criteria, including relevance to AI-enabled HRM, publication period, academic quality, and full-text availability. The selected literature was analyzed using thematic analysis to identify recurring patterns, major themes, and emerging trends related to AI implementation in HRM. The findings indicate that AI adoption has transformed recruitment and selection, employee training and development, performance management, workforce analytics, and strategic workforce planning by improving efficiency, supporting data-driven decision-making, enabling personalized employee development, and enhancing organizational agility. However, significant challenges remain, including algorithmic bias, privacy concerns, lack of transparency, accountability issues, and employee resistance. Successful AI adoption depends not only on technological capabilities but also on organizational readiness, ethical governance, leadership support, and employee acceptance. Unlike previous reviews that primarily examine individual HR functions or specific AI applications, this study provides an integrated synthesis of technological, organizational, strategic, and ethical dimensions within a unified analytical framework, offering a more comprehensive understanding of AI-driven HRM transformation. The findings highlight the importance of balancing technological innovation with human-centered management practices to ensure sustainable and responsible AI implementation.